2017
DOI: 10.4039/tce.2017.22
|View full text |Cite
|
Sign up to set email alerts
|

Do visual cues associated with larger diameter trees influence host selection by Tetropium fuscum (Coleoptera: Cerambycidae)?

Abstract: Tetropium fuscum (Fabricius) (Coleoptera: Cerambycidae) is an invasive phloeophagous beetle established in Atlantic Canada that infests stressed and moribund Picea Dietrich (Pinaceae) species. Successfully colonised trees tend to be large in diameter (>10 cm diameter at breast height), but whether diameter influences host selection, larval performance, or both, is unknown. We tested the hypothesis that T. fuscum host selection is influenced by visual cues associated with tree diameter by counting the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…was not significant, showing that thicker trees are more likely to be hit by flying beetles (Nelson et al, 2017). However, this possibility can be ruled out in our study because we attached sticky sheets of the same size to all the trees, meaning that the number of trapped beetles was equivalent to the number per unit area.…”
Section: Discussionmentioning
confidence: 76%
“…was not significant, showing that thicker trees are more likely to be hit by flying beetles (Nelson et al, 2017). However, this possibility can be ruled out in our study because we attached sticky sheets of the same size to all the trees, meaning that the number of trapped beetles was equivalent to the number per unit area.…”
Section: Discussionmentioning
confidence: 76%
“…Previous research on other Cerambycidae beetles also reported that infested host trees were larger in size [14,15,37]. In terms of host selections, in the case of Tetropium fuscum (Fabricius) (Coleoptera: Cerambycidae), tree size positively affects the landing rate; this relationship is thought to be due to the difference in the chances of adults being passively intercepted on larger versus smaller trees [15]. This passive effect related to tree size is also suggested in the mathematical model for encounter rates in the process of random searching for host trees in tree-boring bark beetles [38].…”
Section: Discussionmentioning
confidence: 97%
“…We showed that larger trees were more susceptible to infestation. Previous research on other Cerambycidae beetles also reported that infested host trees were larger in size [14,15,37]. In terms of host selections, in the case of Tetropium fuscum (Fabricius) (Coleoptera: Cerambycidae), tree size positively affects the landing rate; this relationship is thought to be due to the difference in the chances of adults being passively intercepted on larger versus smaller trees [15].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, their movements are determined primarily by the size and distribution of potential host trees within their habitat (Balogh et al, 2020). Larger diameter trees have more food for developing larvae, resulting in a positive influence of diameter on landing rate (Nelson et al, 2017). Our results are consistent with these previous studies, suggesting that bigger trees harbour more insects and suffer more attacks.…”
Section: Discussionmentioning
confidence: 99%